1992
DOI: 10.1039/c39920001005
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective halocyclization reaction using a chiral titanium complex

Abstract: Enantioselective halocyclizations of diallyl-2-hydroxyacetic acid 1 and 2-hydroxymethylpent-4-en-I -01 6 have been developed using a chiral titanium complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 7 publications
0
38
0
3
Order By: Relevance
“…[9] Prior to further biocatalytic reaction, we thought to correlate the reactivity of the benzylic position with one of the pro-chiral hydroxymethyl groups of compound 1. A stereoselective halocyclization reaction [12] was explored for that purpose. Thus when compound 1 was treated with NIS (1.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Prior to further biocatalytic reaction, we thought to correlate the reactivity of the benzylic position with one of the pro-chiral hydroxymethyl groups of compound 1. A stereoselective halocyclization reaction [12] was explored for that purpose. Thus when compound 1 was treated with NIS (1.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Working model for predicting the enantiopreferences of primary alcohols (2,(11)(12)(13)(14)(15) in PPL-catalyzed kinetic resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(For examples of discrimination of prochiral two olefinic groups by halocyclization using chiral auxiliary, see refs 12-18.) [12][13][14][15][16][17][18] (2)Based on this idea, we studied the intramolecular haloetherification reaction of cyclohexa-1,4-dienes 1 having the C 2 -symmetric acetal on the side chain and found that the reaction discriminated the two prochiral olefins in a highly diastereoselective manner to give 2 as the major product (Chart 1).19) The alkoxy group of the mixed acetals was then converted to an alkyl group. The obtained alkylated compounds 3 were subjected to several transformation reactions forming optically active cyclohexane derivatives with multichiral centers.…”
mentioning
confidence: 99%
“…(For examples of discrimination of prochiral two olefinic groups by halocyclization using chiral auxiliary, see refs 12-18.) [12][13][14][15][16][17][18] (2)…”
mentioning
confidence: 99%